PENGARUH REWARDDAN PUNISHMENT TERHADAP MOTIVASI NASABAH DALAM MEMBAYAR ANGSURAN PADA BADAN USAHA MILIK DESA (BUMDes) MEKAR SARI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Ijul Miswandi (Fakultas Ekonomi Universitas Pasir Pengaraian, 2022)
This study aims to determine how the effect of reward and punishment on customer motivation in paying installments. The population in this study were all BUMDes customers in 2019. The method in this study was a quantitative method, the population in this studywas the total number of BUMDes customers in 2019 totaling 69 respondents. Data collection methods using observation, interviews, questionnaires, the coefficient of determination obtained an R value of 0.837, the results of the study of the variable T testshowed the value of t-count> t-table value (3.732> 1.99656). This shows that the reward variable has a significant positive effect on customer motivation in paying installments, the punishment variable t-value> t-table value (5.703> 1.99656), indicating that the punishment variable has a significant positive effect on customer motivation in paying installments, results from the F test shows the value of F calculated 175.352> F table value 2.74 which means there is a significant influence. So it can be concluded that reward and punishment jointly have a significant effect on customer motivation in paying installments. For further research, those who want to conduct research on the same theme are advised to add other variables that can affect customer motivation in paying installments not found in research this can also be useful for BUMDes or other organizations.